2006
DOI: 10.1074/jbc.m506035200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of P-Rex1 by the Cyclic AMP-dependent Protein Kinase Inhibits the Phosphatidylinositiol (3,4,5)-Trisphosphate and Gβγ-mediated Regulation of Its Activity

Abstract: Rac activation is a key step in chemotaxis of hematopoietic cells, which is both positively and negatively regulated by receptors coupled to heterotrimeric G proteins. P-Rex1, a Rac-specific guanine nucleotide exchange factor, is dually activated by phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ) and the G␤␥ subunits of heterotrimeric G proteins. This study explored the regulation of P-Rex1 by phosphorylation with the cAMP-dependent protein kinase (protein kinase A) in vitro and by G i -and G s -coupled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 43 publications
(75 reference statements)
5
64
0
Order By: Relevance
“…3D). This is consistent with previous reports showing that dephosphorylation of PREX1 by protein phosphatases activates GEF activity (30,31). In addition, PREX1 that was purified from cells co-expressing PAK1 showed reduced GEF activity at multiple PIP 3 concentrations compared with dephosphorylated PREX1, with a significant difference in GEF activation in the presence of 0.1 M PIP 3 .…”
Section: Prex1 Is Phosphorylated Through a Pi3k-dependent Mechanism Dsupporting
confidence: 82%
See 4 more Smart Citations
“…3D). This is consistent with previous reports showing that dephosphorylation of PREX1 by protein phosphatases activates GEF activity (30,31). In addition, PREX1 that was purified from cells co-expressing PAK1 showed reduced GEF activity at multiple PIP 3 concentrations compared with dephosphorylated PREX1, with a significant difference in GEF activation in the presence of 0.1 M PIP 3 .…”
Section: Prex1 Is Phosphorylated Through a Pi3k-dependent Mechanism Dsupporting
confidence: 82%
“…PREX1 is phosphorylated downstream of neuregulin and IGF1 (18,19), and multiple studies have demonstrated that phosphorylation causes an electrophoretic mobility shift in PREX1 (18,30,31). In MCF7 breast cancer cells, we found that insulin also caused a PREX1 mobility shift (Fig.…”
Section: Prex1 Is Phosphorylated Through a Pi3k-dependent Mechanism Dsupporting
confidence: 49%
See 3 more Smart Citations